The Effect Of Service Quality And Promotion On Buying Interest In Fortun Oil (Case Study On Consumers Of S3a Shop In Sirah Pulau Village) - Dewi Oktami; Darwin Kesuma; Mujari Mujari (Universitas Dehasen Bengkulu, 2026)
This study aims to determine how service quality and promotion partially and simultaneously influence purchase intention for Fortune oil (a case study of consumers at the S3A store in Sirah Pulau Village). The sample size for this study was 88 respondents. The sampling method used was incidental sampling. This quantitative study employed multiple linear regression analysis, processed using SPSS, resulting in a regression equation . The results showed a significant effect between service quality and consumer purchasing decisions at the Bintang Mulia Jaya Lubuk Beringin Manggul dealership. Promotion also significantly influenced purchase intention for Fortune oil (a case study of consumers at the S3A store in Sirah Pulau Village). The F-test showed that service quality and promotion simultaneously influenced purchase intention for Fortune oil (a case study of consumers at the S3A store in Sirah Pulau Village).